Scientific landscape of melatonin, its hybrids, and its derivatives as anti-tumor agents: A bibliometric analysis - Andres F. Yepes, Wilson Cardona Galeano, Howard Ramírez-Malule (Journal of Applied Pharmaceutical Science, 2024)
Melatonin (MLT), its derivatives, and its hybrids have been marked beneficial against several human malignancies by inhibiting the growth of different tumors not only under both in vitro and in vivo conditions but also, specially MLT, for the management of cancer in clinical trials. In this study, a bibliometric analysis of peer-reviewed scientific literature on MLT, as well as their derivatives and hybrids published from 1973 to 16 August 2023 is presented. A total of 2792 articles retrieved in Scopus were analyzed and visualized by VOSviewer 1.6.19. The records show a rise in the number of published papers since 2004. In addition, the main areas of knowledge in which the researchers concentrated the studies were: (i) Biochemistry, Genetics, and Molecular Biology, (ii) Medicine, and (iii) Pharmacology, Toxicology, and Pharmaceutics, with 33.9, 32.4, and 10.1% of the records, respectively. Molecular docking studies of MLT and their anticancer activities for several types of cancer appeared as one of the hotspots of this field. The top five most productive countries—in terms of number of published articles—in studies associated with MLT are the United States, China, Italy, Spain, and Germany.
Keywords: Melatonin, hybrids, derivatives, antitumoral activity, bibliometric analysis